Pendampingan Kelompok Belajar Untuk Meningkatkan Kemampuan Numerasi Dengan Metode Gasing - Wewe, Melkior; Latong, Jefrianus; Kori Yusman, Heldiana; Coo Bule, Modesta Venidora; Fono, Maria Adriana (Civiliza Publishing, 2025)
Numeracy abilities are not limited to the ability to apply mathematical concepts to solve problems, but can also be more about practical and critical thinking patterns in various situations in everyday life. This activity aims to provide education and assistance in implementing the Thematic KKN program in accompanying afternoon learning activities at SMP Negeri 1 Boawae which are related to the process of improving students' numeracy skills. The mentoring method consists of three stages, namely preparation, implementation of mentoring, and evaluation of activities. This program successfully creates a learning environment that motivates students to improve their numeracy. The involvement of students as teacher partners brings a fun and interactive learning experience. Learning strategies using fun and enjoyable learning methods have increased students' interest in learning and their problemsolving skills. Apart from that, this program also makes a positive contribution to the development of teachers in implementing effective and enjoyable learning methods for students